Vibration in an Electrically Affected Hygro-magneto-thermo-flexo Electric Nanobeam Embedded in Winkler-Pasternak Foundation - Rajendran Selvamani; J Rexy; Farzad Ebrahami (Mechanics of Advanced Composite Structures)
This paper presents applied electric voltage performance in hydrothermal magneto flexo electric nanobeams embedded in the Winkler-Pasternak foundation based on nonlocal elasticity theory. Higher-order refined beam theory via Hamilton's principle is utilized to arrive at the governing equations of nonlocal nanobeams and solved by implementing an analytical solution. A parametric study is presented to analyze the effect of the applied electric voltage on dimensionless deflection via nonlocal parameters, slenderness, moisture constant, critical temperature, and foundation constants. It is found that physical variants and beam geometrical parameters significantly affect the dimensionless deflection of nanoscale beams. The accuracy and efficiency of the presented model are verified by comparing the results with that of published researches. A good agreement has arrived. The numerical examples are presented to explain how each variant can affect the structure's stability endurance. This type of model and its physical output show the great potential of hygro-magneto-thermo-flexo electric combination in the design of intelligent composite structures and use in structural health scanners. Recent advances in the application of nanotechnology have resulted in the manufacture of nanoelectromechanical devices. The attractiveness of them is due to their excellent and distinctive mechanical and electrical properties.